2019
DOI: 10.1136/bmjgh-2019-001855
|View full text |Cite
|
Sign up to set email alerts
|

Who is telling the story? A systematic review of authorship for infectious disease research conducted in Africa, 1980–2016

Abstract: IntroductionAfrica contributes little to the biomedical literature despite its high burden of infectious diseases. Global health research partnerships aimed at addressing Africa-endemic disease may be polarised. Therefore, we assessed the contribution of researchers in Africa to research on six infectious diseases.MethodsWe reviewed publications on HIV and malaria (2013–2016), tuberculosis (2014–2016), salmonellosis, Ebola haemorrhagic fever and Buruli ulcer disease (1980–2016) conducted in Africa and indexed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 35 publications
6
128
3
Order By: Relevance
“…Local author representation decreased if any of the collaborators were from the USA, Canada or Europe and it decreased even further in collaborations with top US universities 1. Another review reported a similar trend in infectious disease research in Africa2 and this pattern has also been reported elsewhere 3…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Local author representation decreased if any of the collaborators were from the USA, Canada or Europe and it decreased even further in collaborations with top US universities 1. Another review reported a similar trend in infectious disease research in Africa2 and this pattern has also been reported elsewhere 3…”
Section: Introductionmentioning
confidence: 70%
“…And, as explored by both Abimbola12 and Mbaye et al in their recent publication,2 solutions valued by a local researcher tend to be qualitatively different than those of a high-income country researcher. Whereas short term, often external solutions are favoured by foreign funding agencies, local citizen researchers favour the organic, internal means that can take more time.…”
Section: The Deeper Problem Of ‘Gaze’mentioning
confidence: 99%
“…Others have highlighted the ongoing effects of the legacy of colonialism in perpetuating power disparities between HIC and LMIC partners (Eichbaum et al 2020 ; Bleakley et al 2008 ; Whitehead 2016 ). This is seen in healthcare research as well as in medical education research (Mbaye et al 2019 ; Canadian Coalition for Public Health Research 2015 ; Taylor 2018 ; The Lancet Global Health 2018 ). In the area of academic global health, Abimbola eloquently summarizes these concerns: “[T]he growing concern about imbalances in authorship are a tangible proxy for concerns about power asymmetries in the production (and benefits) of knowledge in global health.…”
Section: The Publication Processesmentioning
confidence: 99%
“…The scarcity of true principal investigators in Africa has been lamented by science policymakers, and more recently even by funders (Oyebade 2010; Nature 2005; Mbaye et al . 2019). African ideas are insufficiently pursued because a large proportion of the continent's scientists are unable to articulate, develop scientific careers or commit to research lines, or because they do so through principal investigators elsewhere ( Nature 2005; Ramsay 2001; Droney 2014).…”
Section: Small Bacteriology Laboratories: Impact and Implicationsmentioning
confidence: 99%